Altitudinal gradient affects on trees and stand attributes in Mount Ciremai National Park, West Java, Indonesia - Andes Hamuraby Rozak; Hendra Gunawan (Foresty Faculty of Hasanuddin University, 2015)
Understanding the effect of altitude on trees and stand attributes of tropical forests is crucial for the development of effective management and conservation strategies. However, study on this issue in Mount Ciremai National Park is still lacking. A total of 136 plots were set on the eastern slope of Mount Ciremai in Mount Ciremai National Park and investigated in six different altitudes: 500 m a.s.l., 840 m a.s.l., 1,300 m a.s.l., 1,400 m a.s.l., 1,780 m a.s.l., and 2,530 m a.s.l. The objective of this study was to analyze the effect of altitude to trees and stand attributes i.e. species and family richness, tree density, basal area, and tree biomass. The changes on trees and stand attributes to altitudinal gradient were analyzed using regression analysis. The result showed that tree species number, family number, tree basal area, and tree biomass significantly declined with increasing altitude, meanwhile tree density significantly increased with increasing altitude. These findings indicate a distinct effect of altitude on tree and stand attributes in Mount Ciremai National Park.